Lysine and Methionine plus Cystine for Laying Hens During the Post-Molting Phase - Domingues, C. H. de F. [UNESP] (2012)
One experiment was conducted to evaluate the effect of using different lysine and methionine + cystine levels on body weight recovery, performance, and egg quality of laying hens during the post-molting period. In this trial, 432 Isa Brown layers, with 72 weeks of age, were distributed in 54 cages according to a completely randomized design with six treatments and nine replicates of eight birds each. During the resting period, six diets with different digestible lysine and methionine + cystine levels were used, as follows: 0.48% digestible lysine and 0.43% methionine + cystine; 0.48% digestible lysine and 0.47% methionine + cystine; 0.48% digestible lysine and 0.52% methionine + cystine; 0.56% digestible lysine and 0.50% methionine + cystine; 0.56% digestible lysine and 0.56% methionine + cystine; 0.56% digestible lysine and 0.62% methionine + cystine. Data were submitted to analysis of variance and means were compared at by Tukey's test at 5% probability level. The different lysine and methionine + cystine levels in the diets fed during the resting period significantly influenced layer performance. The diet containing 0.56% lysine and 0.56% methionine + cystine promoted higher egg weight eggs during the second production cycle.